Development of Android Based Information System Media about Plant Diversity in Alas Purwo National Park - Sindi Ayu Astari; Imam Mudakir; Mochammad Iqbal (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
Abstract The aim of this study is to develop Android based information system media about plant diversity in Alas Purwo National Park. This study is a developmen reserach using a 4-D development model (4 D model . Data collection methods used in this study were interviews, documentation, and expert validations. The result of this study about the validation of android based information system was all off expert validation evaluated this media very valid with a percentage of 89.55% in category quantitative assessment. In qualitative assessment, these media need to little modification such as in use of a source of the picture and more efficient to explant about plant description in the media